'It clarified a lot': GP trainees as peer role players in a formative Clinical Skills Assessment (CSA). Issue 2 (4th March 2021) - Bell, Elizabeth Anne; Cleland, Jennifer; Gambhir, Nitin
ABSTRACT: Introduction: The MRCGP Clinical Skills Assessment (CSA) is a high stakes examination which a significant proportion of candidates fail on first sitting. To address this, deaneries have introduced candidate preparation, such as formative CSAs (f-CSA). One way to maximise the gains from a f-CSA is to use GP trainees as peer-role players (VRPs) instead of professional actors. Our aim was to explore trainee experiences of, and educational gains from, the VRP role. Method: This qualitative study used semi-structured interviews to explore 15 VRPs' perceptions of peer roleplay. Questions were generated from the literature and from informal discussions with f-CSA organisers. Analysis was inductive and thematic. Results: Analysis identified three main themes. Role play gave participants insight into the exam in terms of what to expect and how to approach the exam. They commented on learning the importance of communication skills and acknowledging the patient's perspective. Finally, there were gains in terms of professional development, particularly in terms of observing good feedback. Discussion: GP trainees who role played patients in a formative CSA reported increased confidence and educational gains from their experience. Whether these perceived gains will be transferred to their own CSA performance later in training remains to be seen.